PERANCANGAN GAME VISUAL NOVEL SEBAGAI SARANA EDUKASI BENCANA TSUNAMI - Putra Dharma, Wisnu Wardhana; Khrisne, Duman Care; Arsa Suyadnya, I Made (Jurnal SPEKTRUM; Vol 11 No 2 (2024): Jurnal SPEKTRUM, 2024)
Educational games about early warning against tsunami disasters can be of interest to school children at an early age to expand information about prevention or develop an early warning system for tsunami disasters. This research aims to make a visual novel role-playing game as a means of educating about the tsunami disaster and finding out the usefulness of games in providing information about the tsunami disaster. Using Ren'py software, the tsunami disaster educational Visual Novel Game was developed and built intelligently, resulting in an application that runs on Windows and Android-based devices. With an average score of 86.1, the System Usability Scale test findings. The design of a Visual Novel Game as a means of educating about the tsunami disaster is considered very good.